SUKU ANAK DALAM BATIN 9 DAN KONFLIK SERIBU HEKTAR LAHAN SAWIT ASIATIC PERSADA - Pujiriyani, Dwi Wulan; Puri, Widhiana Hestining (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
This paper seeks to explore the case of conflict within palm oil plantation-local people partnership involving SAD Batin 9 group with palm oil company. Bungku village was the site chosen to take this issue comprehensively.The expansion ofpalm oil plantationshave led totheloss ofliving territoryto developtheir social system. Conflictsarisenot onlyverticalbut alsohorizontal. Amongst the Inner SAD 9 itself, each fighting for its sovereignty emerged. SAD groups which were impoverished by imbalanced control structure eventually have to deal with a part of their own group which slowly became part of the new ruling capital group. The palm oil skipper that came from a group of local residents as well as newcomers were the form of the emerging plantation power. In the context of adverse incorporation, they were part of the group that get benefit from the presence of palm oil plantation. Involvement or integration of this group in the oil business scheme has allowed them to accumulate new capital sources. This group could accumulate greater profits from palm-oil they collect from small farmers. Key words: Suku Anak Dalam, palm oil, conflict, partnership